Abordagem metabolômica aplicada ao estudo da relação microambiente, sazonalidade, perfil químico-atividade biológica em Schinopsis brasiliensis - Luz, Licia dos Reis (2023)
Schinopsis brasiliensis Engl. (braúna) is a tree species from the Anacardiaceae family, typically found in the caatinga biome. This versatile tree species has a wide range of applications, especially in the therapeutic, ornamental, and industrial fields. However, there is a scarcity of information regarding the comparison of the metabolic profile of leaves and bark from the species in different seasons and microenvironments, both in terms of chemical composition and pharmacological properties. In this study, the influence of environmental factors and sample collection periods on braúna was investigated over several years, using multivariate statistical analyses in conjunction with nuclear magnetic resonance (NMR) and liquid chromatography-mass spectrometry (LC-MS). Bark samples from different areas and collections exhibited distinct metabolic profiles, influenced by various environmental factors such as water stress, rainfall, solar radiation, and temperature. Therefore, by correlating metabolic data with climatic information, it becomes evident how abiotic factors influence metabolite production in braúna bark. These findings can assist in the assessment of quality and biological properties in S. brasiliensis, providing valuable insights into the chemical ecology of this species. In leaf samples, 45 compounds, including isomers, were tentatively identified. Chemometric analyses efficiently distinguished leaf samples from different seasons, identifying 23 potential biomarkers associated with enhanced cytotoxic activities exhibited by the reserve area's leaves during the June period. This collection displayed the lowest IC50 value for the MDAMB-231 lineage, along with the best selectivity index value. These results demonstrate significant potential for the plant, which can contribute to adding value to this biodiversity asset.